Peacebuilding - Mac Ginty, Roger (Sage library of international relations, 2014)
This new 4-volume Major Work showcases the main debates and controversies associated with peacebuilding. In particular, this collection seeks to go beyond a simple explanation of peacebuilding institutions and projects to unpack the ideas and ideologies that underpin the subject. Recent years have seen a large increase in the academic and policy literature on peacebuilding. They have also seen significant successes and failures in peacebuilding, reforms among international organisations (such as the United Nations and World Bank), and increased prominence awarded to local peacebuilding actors. The articles in this major work capture these changes and collectively present a state-of-the-art account of contemporary peacebuilding.